TELAAH KURIKULUM PENDIDIKAN: DINAMIKA PERUBAHAN PENERAPAN KURIKULUM DI INDONESIA - Afifah Qodri Rinjani; Mimi Mulyani; Ratna Rosita Pangestika (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2024)
This article provides a critical review of the education curriculum in Indonesia starting from the implementation of the Competency Based Curriculum (KBK) which was implemented in 2004 to the Merdeka Curriculum which has been implemented since 2022. Through a systematic review method, this research seeks to analyze curriculum developments with a focus on the Based Curriculum. Competencies (2004), Education Unit Level Curriculum (2006), 2013 Curriculum, revised 2013 Curriculum, and Merdeka Curriculum. The results of the review show that each curriculum has a positive impact on students and the education system and has its own unique obstacles. The Competency-Based Curriculum emphasizes the development of generic skills and student character, while the Merdeka Curriculum emphasizes learning freedom and learning recovery as a response to the Covid-19 pandemic. From the analysis of the various curricula, it can be stated that learning from each curriculum is important for forming a future curriculum that is adaptive, high quality and in line with educational needs in Indonesia.